Analisis Unsur Yang Mempengaruhi Hubungan Antara Pekerja dan Pengusaha - Dana Prihadi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This research was conducted to determine workers' perceptions about the laws and regulations in the work environment, the existence of trade unions and the harmonization of relations between workers and employers. The researcher carried out several stages, the first that was carried out was to measure the influence of understanding of regulations in the field of manpower, second to measure workers 'perceptions of work welfare, third to measure the effect of workers' perceptions on the existence of workers, and fourth to measure the harmonization between workers and employers using alpha values cronbach of 0.6. The research used multiple linear regression analysis tools and classical assumption test. The results of this study indicate a positive and significant influence among workers' perceptions of the invitational regulations in the labor sector. Prosperity of the workforce and harmonization of relations between workers and employers simultaneously.